2019
DOI: 10.1155/2019/9817930
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rising Temperature on Lyme Disease:Ixodes scapularisPopulation Dynamics andBorrelia burgdorferiTransmission and Prevalence

Abstract: Warmer temperatures are expected to increase the incidence of Lyme disease through enhanced tick maturation rates and a longer season of transmission. In addition, there could be an increased risk of disease export because of infected mobile hosts, usually birds. A temperature-driven seasonal model of Borrelia burgdorferi (Lyme disease) transmission among four host types is constructed as a system of nonlinear ordinary differential equations. The model is developed and parametrized based on a collection of lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 56 publications
1
23
0
Order By: Relevance
“…The process based model used to investigate multiple intervention strategies is based on a prior model of the tick vector for Lyme Disease, Ixodes scapularis [ 24 , 25 , 26 ]. Dynamic compartments for maturing, questing, and feeding larvae, nymphs and adults were included for both infected and uninfected populations, as well as population dynamics of host species, represented as a system of ordinary differential equations.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The process based model used to investigate multiple intervention strategies is based on a prior model of the tick vector for Lyme Disease, Ixodes scapularis [ 24 , 25 , 26 ]. Dynamic compartments for maturing, questing, and feeding larvae, nymphs and adults were included for both infected and uninfected populations, as well as population dynamics of host species, represented as a system of ordinary differential equations.…”
Section: Methodsmentioning
confidence: 99%
“…Other population parameters were drawn as necessary from the study by Ioffe-Uspensky et al (1997), with the exit rate of ticks from the feeding compartments based on stage-dependent feeding times, as well as average clutch size and exit rate of the pre-oviposition period, which was corroborated by a second study [ 18 , 36 ]. Egg hatching rates are known to be temperature dependent, however not enough data was found to give a response curve [ 37 ], so the rate was borrowed from a prior modeling study [ 24 ]. Median time of larval hardening was taken from Koch and Tuck, and interpreted as a half-life [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean annual temperature was identified as a potential predictor of human outdoor activity which could correlate with exposure to ticks [ 38 , 41 ]. It is important to note that temperature also impacts tick densities and activity and is unlikely to explain much of the variability in human outdoor activity behaviour [ 42 ]. The mean annual temperature for each county was obtained from the US Climate Divisional Database through the National Oceanic and Atmospheric Administration (NOAA) [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…al. [26] conducted a modeling study that evaluated the effect of rising temperatures on these ticks and the primary disease that they transmit, Lyme disease. They found that rising temperature has the potential to increase transmission risk to humans due to higher tick numbers and a longer season of transmission.…”
Section: Introductionmentioning
confidence: 99%